Study of Students’ Misconceptions of Additive Color Mixing and Color Absorption - ชูสกุล, พชร; แนมจันทร์, กิตติศักดิ์ชัย; รัตนานุพงศ์, พันเทพ; สามารถ, พิชิต; กลั่นบุศย์, แสงกฤช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objective of this research was to develop a test for measuring students’ misconceptions about the combination of colored light and the absorption of colored light by a screen, and to examine the Misconceptions of 39 Grade 12 students in the Science–Mathematics program in the 2025 academic year. A 10-item test covering three learning objectives was administered. The test was evaluated for quality and found to be suitable for use. The results indicated an average misconception rate of 70%. By learning objective, the highest misconception rate was found for the second objective explaining the outcomes of combining colored light and the effect of light intensity at 77%. The most prominent misconception was the belief that yellow light is a primary color 57%. The second most common misconception was the belief that when two primary colors are projected onto a screen, the screen reflects the combined color without absorbing it 54%. Misconception, Additive Color Mixing, Absorption of Colored Light by a screen.